Modern slavery and human trafficking the victim journey - Murphy, Carole; Lazzarino, Runa (Policy Press, 2023)
Throughout the world, vulnerable subjects are being deceived into entering an abusive journey, in the organ trade, exploitative labour business, and forced criminality - and their lives will never be the same. This book traces the journey of victims/survivors of modern slavery and human trafficking into and within the UK, from recruitment to representation to (re)integration. Using global comparative case studies, it discusses recruitment tactics and demand, prevention in supply chains, issues with effective legal protection and care services, vulnerability to re-trafficking and the ideological misrepresentation of vulnerable migrants and victims/survivors in media, the film industry, legislation, and more